HIV-1 macrophage tropism is determined at multiple levels of the viral replication cycle. - Fouchier, R A (1994)
The ability of HIV-1 to infect macrophages is thought to be essential in AIDS pathogenesis. We tested the ability of 19 primary virus isolates to infect monocyte-derived macrophages (MDM) from different donors. Two HIV-1 isolates were able to establish a productive infection in MDM from all donors tested, whereas eight completely lacked this capacity. Next to these isolates with extreme phenotypes, 50% of the primary isolates under study displayed an intermediate phenotype. These intermediate macrophage-tropic isolates established a productive infection in MDM from some but not all donors tested. PCR analysis demonstrated that the capacity to replicate in MDM could be determined at the previously described level of virus entry. However, for intermediate macrophage-tropic isolates replication was abrogated at the level of reverse transcription. Entry of highly macrophage-tropic isolates resulted in efficient completion of the reverse transcription process, whereas entry of intermediate macrophage-tropic isolates did not. Our experiments indicate that primary HIV-1 isolates may differ in their dependency on cellular factors required for reverse transcription in MDM. Differences in susceptibility of MDM for in vitro HIV-1 infection suggest variation in the availability of these cellular factors between MDM from different individuals.